Assessing the worker’s performance based on safety management aspect implemented case study at Ladang Zamrud, Johor / Farid Amani Abdul Rahman - Abdul Rahman, Farid Amani (Faculty of Plantation and Agrotechnology, 2018)
This study was conducted to assess the worker’s performance based on safety management aspect where’s case study happened at Ladang Zamrud, Johor. Worker’s performance is crucial to every oil palm plantation’s to determine the productivity of the worker’s involve. Daily work without proper knowledge of safety management led to the problems of a worker’s including lowering the safety, productivity and performance. Decision of either to follow or abandon the importance of safety management was made by the workers themselves which were influenced by their knowledge and awareness regarding the safety management in the plantation estate. However, these factors has not been measured properly in order to determine their significance towards the worker’s practices. Hence, a survey has been conducted to determine the proposed measurement in oil palm plantations area at Ladang Zamrud, Johor. Workers from the research area were interviewed using questionnaire as the main instrument. The questionnaire has been pretested prior to the actual survey. A total of 85 workers were sampled out of 85 worker’s population. Data were analyzed for their central tendencies as well as significant relationship. Result showed that knowledge has given a significant effect to the worker’s practices towards worker’s performance in oil palm estate. On the other hand, the findings also found that the awareness level is inadequate among workers. For that reason, there is a need for continuous awareness program by the estate management regarding the worker’s performance in the oil palm estate.